Sistem Pakar Diagnosa Penyakit Kista Ovarium dengan Metode Forward Chaining - Aggy Pramana Gusman; Dian Maulida; Eva Rianti (Universitas Putra Indonesia YPTK Padang, 2019)
Ovarian cyst disease can only attack women after 25 years old of age and above the lack of public knowledge about the symptoms of ovarian cyst disease is the problem, therefore the authors make an expert system diagnosing ovarian cyst disease with a forward chaining method where patients consults with how to answer a number of questions related to the symptoms of an ovarian cyst and the patients answers questions according to the symptoms felt by the patient. This expert system is created using the PHP programming language and MYSQL database. It is expected that with an expert system of diagnosing ovarian cyst disease, later it can facilitate patients in consulting about his ovarian cyst disease and can increase knowledge for the patient